Investment risk management and energy efficiency, considering capital and operating expenditure in industrial development - Rudnieva, I. (Ways to Improve Construction Efficiency, 2020)
The article clarified the impact of investment risk management on energy efficiency as a significant factor affecting the cost of an industrial development project. The effective implementation of any new construction or reconstruction project is inextricably linked with financial risk management, that allows take into account all possible expenditures that are not only once spent on its implementation (capital expenditures), but also operational expenditures that will be incurred when it is transferred into operation. A very important problem is the assessment of the real cost of the project, taking into account the operational expenditures during the life cycle of the building, as well as the optimization of both the capital expenditures (CAPEX) of the development company and the operational expenditures (OPEX). The implementation of development projects can be divided into three main stages: pre-investment, investment and operational. The sources of possible successes or failures in the implementation of entrepreneurial development projects are questions that are usually laid down in the early stages of organizing the construction of real estate objects. Therefore, the most important feature in the construction projects management in the field of industrial development is taking into account the dominant influence exerted on the efficiency of the first, pre-investment, phase. As a result, it allows to obtain significant cost-savings in the total cost of the project. All this requires to analyze various design solutions due to the Investor's desire to optimize capital expenditures, which will significantly reduce the costs of some project design solutions. Considering the above, a calculation algorithm is proposed to determine the total cost of the building's life cycle. During the research, an economically and energy-efficient model of using the enclosing structure for an industrial building was determined, which allows obtaining significant costs-savings, taking into account the operational expenditures during the life cycle of the building.